The principle of multilayer plane-parallel structure antireflection - Kosoboutskyy, Petro; Karkulovska, Mar’yana; Morgulis, Alla (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The principle of two- and three-layer transparent system antireflection is based on the method of Fabry–Perot multiple-beam interference spectrum envelopes and it is shown that the presence of half-wave and quarter-wave layer thicknesses or their combination is sufficient but not necessary for its achievement. The necessary condition is the condition of overlapping of interference layer envelopes, therefore the antireflection effect can be observed at arbitrary ratios of optical layer thicknesses, angles of incidence and optical refraction index of media when the condition is satisfied for the minimum of interference contour in the required spectral region.
Optica Applicata, Vol. 40, 2010, nr 4, s. 759-765
Keywords: optyka; Fabry–Perot interference; antireflection; envelope function